2013
DOI: 10.1007/s12291-013-0317-0
|View full text |Cite
|
Sign up to set email alerts
|

“P53 Codon 72 Single Base Substitution in Viral Hepatitis C and Hepatocarcinoma Incidences”

Abstract: Viral infection with hepatitis C virus (HCV) has a high propensity in becoming chronic and it is the major cause of hepatocellular carcinoma (HCC) worldwide. This review was basically established to illustrate the putative role of the P53 gene Arg72Pro polymorphism on various cancer models and viral infections, focusing on HCV and HCC incidences. Authors studied the 72 G/C single base substitution of P53 gene at codon 72 using various polymorphic techniques. Intriguingly, authors investigated that the P53 codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Nonetheless, more and more meta-analysis evidence obtained by pooling all the currently available case-control studies to estimate the effect and distribution of p53 codon 72 Arg/Pro polymorphism on cancer susceptibility has indicated that the polymorphism is not associated with overall cancer odds in several populations, including Iranian [ 41 ] and Chinese [ 42 ] colorectal cancer patients [ 43 ]. However, others studies have indicated the opposite, that is, that the polymorphism is associated with increased risk of several malignancies associated with viral infections, including in Caucasian (prostate cancer) [ 44 ], European (high-grade glioma; Pro 72) [ 45 ], Indian (cervical cancer) [ 46 ], Chinese (cervical cancer) [ 47 ], and Japanese (hepatocellular carcinoma) populations [ 48 ], implying that important ethnic and tumor type differences may exist regarding the cancer susceptibility of p53 codon 72 polymorphisms. Although our data could not show whether a given p53 codon 72 polymorphism is a risk factor, such polymorphisms may have an influence on GBM susceptibility in combination with certain other elements.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, more and more meta-analysis evidence obtained by pooling all the currently available case-control studies to estimate the effect and distribution of p53 codon 72 Arg/Pro polymorphism on cancer susceptibility has indicated that the polymorphism is not associated with overall cancer odds in several populations, including Iranian [ 41 ] and Chinese [ 42 ] colorectal cancer patients [ 43 ]. However, others studies have indicated the opposite, that is, that the polymorphism is associated with increased risk of several malignancies associated with viral infections, including in Caucasian (prostate cancer) [ 44 ], European (high-grade glioma; Pro 72) [ 45 ], Indian (cervical cancer) [ 46 ], Chinese (cervical cancer) [ 47 ], and Japanese (hepatocellular carcinoma) populations [ 48 ], implying that important ethnic and tumor type differences may exist regarding the cancer susceptibility of p53 codon 72 polymorphisms. Although our data could not show whether a given p53 codon 72 polymorphism is a risk factor, such polymorphisms may have an influence on GBM susceptibility in combination with certain other elements.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparing acute hepatitis C and HCC have not found any association between codon 72 polymorphism and disease severity or HCC(Eskander et al, 2014;Hu et al, 2014). The inconsistency in association and prevalence observed could be attributable to geographical, environmental or ethnic differences in the studied population.…”
mentioning
confidence: 66%
“…Moreover, the understanding of the phenotype-genotype correlation is difficult due to modifying factors in thalassemia [ 2 ]. Several studies have been demonstrated that the occurring variation in some genes, such as HBA1, HBA2, HBB, HBG1, HBG2, BCL11A, COL1A1, CAT and GST genes can moderate the severity of thalassemia [ 16 , 17 , 18 , 19 , 20 ]. Recently, several studies have evaluated the effect of 3'-UTR SNPs on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the genes related to the severity of thalassemia intermedia (TI) were extracted from known literatures [ 16 , 17 , 18 , 19 , 20 ]and the mRNA expression profile and molecular functions of these genes were obtained. Then, miRNA target site SNPs were predicted by in silico analysis.…”
Section: Methodsmentioning
confidence: 99%